2014
DOI: 10.1063/1.4876924
|View full text |Cite
|
Sign up to set email alerts
|

The sidewall-localized mode in a resonant precessing cylinder

Abstract: We investigate, via direct numerical simulation using a finite-element method, the precessionally driven flow of a homogeneous fluid confined in a fluid-filled circular cylinder that rotates rapidly about its symmetry axis and precesses about a different axis that is fixed in space. Our numerical simulation, after validating with the asymptotic analytical solution for a weakly precessing cylinder and with the constructed exact solution for the strongly nonlinear problem, focuses on the strongly precessing flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Instead, we see free Kelvin modes solely with retrograde drift motion which on the one hand agrees with experimental observations of inertial waves in a spherical Couette experiment with liquid sodium (Kelley et al 2007). On the other hand, they seem to contradict with the results from Albrecht et al (2015a) who show that at Re = 2482 (close to the threshold of the instability) the growth rate is very small resulting in a very long time required for the triadic resonance to emerge (which explains why Kong et al (2014) did not find the triadic resonances at the same parameters). However, the reason for the disappearance of the triads at larger Reynolds number is probably an instability of the m = 1 mode, which occurs close to the fundamental resonance due to the increased efficiency of the forcing, while around Γ = 1.825 or Γ = 2.2 the m = 1 mode may saturate by viscosity before becoming unstable.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Instead, we see free Kelvin modes solely with retrograde drift motion which on the one hand agrees with experimental observations of inertial waves in a spherical Couette experiment with liquid sodium (Kelley et al 2007). On the other hand, they seem to contradict with the results from Albrecht et al (2015a) who show that at Re = 2482 (close to the threshold of the instability) the growth rate is very small resulting in a very long time required for the triadic resonance to emerge (which explains why Kong et al (2014) did not find the triadic resonances at the same parameters). However, the reason for the disappearance of the triads at larger Reynolds number is probably an instability of the m = 1 mode, which occurs close to the fundamental resonance due to the increased efficiency of the forcing, while around Γ = 1.825 or Γ = 2.2 the m = 1 mode may saturate by viscosity before becoming unstable.…”
Section: Discussionsupporting
confidence: 41%
“…Kerswell (1999) showed that a geostrophic instability even if it is subdominant to the triadic instability should finally outweigh the triad if Re is large enough because it does not suffer from detuning effects. This may be important for the observation of large mean ciculations in experiments but cannot explain alone the abrupt transition to a chaotic flow which is determined by the precession ratio and hardly depends on Re (Kong et al 2014. This does not mean that the geostrophic mode does not matter for this phanomenon, but in order to be able to judge this more simulations are required at larger Γ.…”
Section: Azimuthal Shear Flowmentioning
confidence: 98%
“…A numerical experiment at Ek = 5 × 10 −5 in the spherical-like cylinder, which is reported in a recent Letter (Kong et al 2014), reveals the existence of strongly precessing flow in the form of a wall-localized mode when Po/ √ Ek = O(10), whose structure is profoundly different from that of weakly precessing flow. The experimental study by Mouhali et al (2012) also indicates the existence of the strongly nonlinear wall-localized mode.…”
Section: Introductionmentioning
confidence: 94%
“…We believe that the small scale fields are related with viscous boundary layer instabilities. 34,35 The magnetic fields are extended upward to outside of the fluid domain. Since the magnetic potential decays as (1/r) l+1 outside the fluid domain, the field outside is mostly dipolar or quadrupolar.…”
Section: B Dynamos Driven By Large Scale Cyclonic Vorticesmentioning
confidence: 99%